Concept of Islamic Education Psychology - Karina Atriyatul Zanah; Erni Isnaeniah (Gunung Djati Conference Series, 2021)
This study aims to discuss the psychology of Islamic education. The research method is a qualitative type through literature study. The approach to data interpretation used content analysis. The results and discussion of this study include the understanding of educational psychology, the concept of Islamic education psychology, and the role of Islamic education psychology. This study concludes that psychology is closely related to Islamic education. As for Islamic education, the psychology that is used as a reference is psychology that originates from the Al-Quran and Hadith.